Assessment of Computer Vision Syndrome and Personal Risk Factors among Employees of Commercial Bank of Ethiopia in Addis Ababa, Ethiopia. (7th May 2021) - Derbew, Haile; Nega, Ansha; Tefera, Worku; Zafu, Tekie; Tsehaye, Kenfe; Haile, Kebede; Temesgen, Belsity
Abstract : Background . Computer vision syndrome (CVS) is an amalgam of visual symptoms caused by continued use of computers. Worldwide, up to 70 million workers are at risk for computer vision syndrome resulting in reduced productivity at work and reduced quality of life. Bank employees are among the risky workers with unknown magnitude of the syndrome. Therefore, the main aim of this study was to determine the prevalence of CVS and its associated personal factors among employees of Commercial Bank of Ethiopia. Methods . A total of three hundred and fifty-nine bank workers participated in the study between February and March 2018. A self-administered structured questionnaire was used to collect sociodemographic data, CVS symptoms, and its personal factors. Snellen chart tool was used to measure blurred vision. Data entry and analysis were performed via Epi Info™ 7 and Statistical Package for the Social Sciences (SPSS) version 21. Binary logistic regression and multivariable logistic regression were performed to assess the association and control the potential confounders. Result . The prevalence of computer vision syndrome in the last 12 months among the total study subjects, 359 (98% response rate), was 262 (74.6%) (95% confidence interval [CI] = 70.1, 79.5). Risk factors that could not be intervened with were sex (AOR: 1.8; 95% CI (1–3)) and age group (AOR: 3.11; 95% CI (1.2–8)). Causal factors that could be intervened with were use of electronic materials outside work (AOR: 3.11; 95% CI (1.15–8.36). Protective factor that could be intervened with was habit of taking a break (AOR: 0.44; 95% CI (0.3–0.8)). Conclusion and Recommendation . Three-fours of the employees were at risk. Sex, age, habit of taking a break, and use of electronic materials outside work environment were significantly associated with the presence of CVS. Remedial actions need to be considered at individual level.